THE IMPORTANCE OF THE DEVELOPMENT OF SPEECH OF CHILDREN OF EARLY AGE - Rimbayeva Ozoda Bazarbayevna (International Journal of Business, Law and Political Science, 2024)
a person lives in a social environment throughout his life, and in this environment speech becomes the main means of communication for a person. Human speech begins to develop from birth through imitation of adult speech. This article will talk about the importance of the development of speech of early children